Public Perception on Water Pricing in Penang - Navamney, Linges; Mou, Leong Tan; Ngai, Weng Chan; Wai, Leng Phang (European Publisher, 2019)
Increasing demand and consumption in water threatens water security and is a hindrance to achieve the Sustainable Development Goal (SDG) 6 – Clean Water and Sanitation. As a developing country, Malaysia is still highly dependent on water resources to support economic growth for agriculture, industry and domestic consumption. Penang state records the highest domestic water consumption in the country although it is considered a water-stressed state. The state government has employed integrated water management to sustain the water supply and reduce consumption. Water pricing is one of the approaches that can be used for both supply management and the control of demand management. This paper aims to examine the relationship between the demographic characteristic as factors affecting the water consumption of the Penangites with the perception of water price through a questionnaire survey. A total of 341 respondents from the north-eastern part of George Town, Penang, were randomly selected in this research. The analysis was carried out using SPSS to run the Chi-square test, whereby the p-value is used to indicate the relationship between each demographic variable with Penangites' perception of water tariff. The results show that only age and gender have a significant relationship with the perception of water price. Besides that, there is no significant relationship among education level, income and ethnicity on perception of water price. The research concludes that Penang’s water tariff could be reviewed and increased in terms of different block tariff as one of the mechanisms to reduce domestic demand and consumption.